Gel-tape casting as a novel method for the production of flexible fine-grained alumina sheets. Issue 7 (July 2020) - Stastny, Premysl; Chlup, Zdenek; Trunec, Martin
Abstract: The paper reports on the development of a new aqueous gel-tape casting method for processing nanosized powders into thin fine-grained sheets with a high relative density after sintering. The method was based on casting a low-viscosity slurry into a tape, using the doctor-blade method and gelling the slurry after the casting. The gelled tape was removed from the tape carrier without any solvent evaporation and the drying of the gelled tape was performed later in a climate box under controlled temperature and humidity. The epoxy-based ceramic slurry could be prepared with a solid loading of 42 vol.%. Ceramic sheets with flat and smooth surfaces were prepared in a thickness range from 0.08 to 0.4 mm after sintering. The sintered sheets reached a relative density of 99.4%, with an average grain size of about 1.1 μm. The strength and flexibility of alumina sheets were investigated and discussed.